GAMBARAN KEPATUHAN MINUM OBAT PADA ANAK DENGAN PENDERITA EPILEPSI DI RSUD PAMBALAH BATUNG - Suci, Novita; Wijaksono, M. Arief; Syahlani, Ahmad; ulumuddin, Muhammad Ihya (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background: Epilepsy is a chronic disease with a high incidence rate, especially in developing countries because the health service system has not been successful in eradicating the causes of Epilepsy. Epilepsy is like other chronic diseases, its recurrence can be controlled by compliance with taking medication. Epilepsy treatment is carried out over a long period of time, perhaps even for the patient's lifetime, however, long-term regular use of medication increases the risk of non-compliance with treatment. Objective: To determine treatment compliance in children with epilepsy at Pambalah Batung, Hospital. Method: Quantitative research with observational descriptive design. The sample consisted of 25 parents of children with epilepsy who sought treatment at the Children's Polyclinic at Pambalah Batung, Hospital in April 2024. Data were analyzed using univariate analysis. Results: Children with epilepsy range in age from 1 year to 9 years. The duration of epilepsy was less than 3 months for 22 people (88%) and more than 3 months for 3 people (12%). Compliance with treatment in children with epilepsy was high as many as 24 people (60%) and moderate compliance as many as 9 people (36%). Conclusion: Most children with epilepsy have high medication compliance and a small number have moderate compliance. It is hoped that Pambalah Batung, Hospital will continue to provide health education to patients and families about caring for epilepsy sufferers at home and always recommend that they comply with the consumption of antiepileptic drugs to avoid repeated seizures or other undesirable things. Keyword: Epilepsy; Medication Compliance